ChemInform Abstract: Click‐Chemistry Approaches to π‐Conjugated Polymers for Organic Electronics Applications. Issue 46 (October 2016) - Marrocchi, Assunta; Facchetti, Antonio; Lanari, Daniela; Santoro, Stefano; Vaccaro, Luigi
Abstract: Review: [46 refs.